Civil Servant Housing and Regional Governance: A Strategic Asset for South Papua’s Capital Development - Achya, Syahriana Hannan Fathya; Suhadi, Suhadi; Fikri, Muhammad Adymas Hikal; Wardono, Ahmad Ali; Dewi, Sisilia Putri (Indonesian Journal of Agrarian Law, 2024)
South Papua Province, as a newly established autonomous region, urgently requires basic infrastructure, particularly housing for Civil Servants (ASN), to support the smooth operation of government administration. One sustainable solution to address urban land limitations is the construction of vertical housing or apartment buildings (Rusun). This study aims to analyze the strategic role of apartment housing for civil servants in South Papua and examine the legal framework as well as socio-spatial implications of vertical housing development. The research employs a normative juridical method with a qualitative approach, focusing on library research of statutory regulations and legal doctrines on apartment housing, along with official documents related to the construction of ASN Rusun. The findings reveal that state-owned apartment housing plays a crucial role in achieving equitable development, improving the welfare of civil servants, and ensuring efficient governance. The legal framework under the Apartment Law emphasizes collective ownership rights, professional management, and legal certainty of ownership. The development strategy of ASN apartments in South Papua reflects strong collaboration between central and local governments in addressing housing challenges in a newly established province.